A primary school-based dengue solution model for post-COVID-19 in southern Thailand: Students understanding of the dengue solution and larval indices surveillance system. - Jiraporn Jaroenpool; Sarunya Maneerattanasak; Femi Adesina; Atchara Phumee; Muhammad Haroon Stanikzai; Chumpon Ponprasert; Yingqin Zheng; Shamarina Shohaimi; Truong Thanh Nam; Temesgen Anjulo Ageru; Amin Nordin Syafinaz; Charuai Suwanbamrung (PLoS ONE)
One of the consequences of the COVID-19 lockdown is that it hinders school-based dengue management interventions. This is due to the closure of schools and the limited availability of online lessons in certain schools. Conversely, the level of basic understanding that primary school children have about the condition is directly related to their likelihood of getting it and their ability to modify their behaviour to prevent it. Thus, the study aims to assess the understanding and develop a school-based model intervention for dengue solutions and larval indices surveillance systems suitable for primary schools. The study used a purposive and convenience technique to recruit participants in the Keawsan sub-district in Nabon district, Nakhon Si Thammarat province, Thailand. An applied community participatory action research (CPAR) design was used to develop a school-based model intervention. The pre-test result shows that more than 90% and 100% of the students have a poor understanding of dengue solutions (UDS) and larval indices surveillance systems (ULISS), respectively. The students with good scores on UDS increased from 2.9% to 54.6% after the intervention, and there is still a prevalent lack of good understanding among more than 85% of the students on ULISS. Meanwhile, gender, class, and school significantly influence (p <0.05) UDS and ULISS among students in either the pre-test or post-test. Based on the thematic analysis, it was determined that the students had learned about dengue fever transmission, dengue mosquitoes, container index calculation, dengue symptoms, and how to prevent dengue mosquitoes, among other topics. Overall, it was discovered that the trained students could convey their knowledge of the dengue solution and the larval indices surveillance system to other students. We recommend that further ULISS training be provided for schoolchildren in more simple terms that they can understand.